INDEKS KESIAPAN STAF PUSKESMAS DALAM PEMBELAJARAN JARAK JAUH DENGAN ELECTRONIC LEARNING DI PROVINSI PAPUA - Soemedi Hadiyanto (JURNAL PENDIDIKAN ROKANIA, 2021)
E-Learning has becoming a crucial learning method since Corona Virus has spread out. In order to implement this method and get the best result of learning, we need to measure the readiness of the staffs in public health centres in Papua Province as their literacy of information, communication and technology are considered limited. The purpose of this research is for measuring and analysing the readiness level index of the staffs. Methodology: Data was analyzed by descriptive quantitative approach, collected from 90 respondents out of 30 public health centres in Papua Province purposively during 21 to 31 October 2020. The measurement and analysis tools are questionnaire, SPSS for Windows and Pearson correlation test. Results: The score of readiness level is 45.99 which is categorized as less prepared for the staffs to conduct e-learning activity. Each parameter and its statistical score are described as follows: technology access: 59.09 (quite ready); the basic computer ability: 51.49 (quite ready); the internet ability: 49.57 (not ready); utilizing software application ability: 42.67 (unprepared); online training participation: 19.25 (unprepared); social support: 57.67 (quite ready); and skill of using online application: 42.27 (not ready). The scores of online training participation and utilizing software application ability are below the total readiness index. Conclusion: The staffs of public health centres are considered as unprepared for conducting independent e-learning activity, inspite of quite good internet access and social supports condition.